Cortical activation to object shape and speed of motion during the first year - Wilcox, Teresa (Neuroimage, 2014)
A great deal is known about the functional organization of cortical networks that mediate visual object processing in the adult. The current research is part of a growing effort to identify the functional maturation of these pathways in the developing brain. The current research used near-infrared spectroscopy to investigate functional activation of the infant cortex during the processing of featural information (shape) and spatiotemporal information (speed of motion) during the first year of life. Our investigation focused on two areas that were implicated in previous studies: anterior temporal cortex and posterior parietal cortex. Neuroimaging data were collected with 207 infants across three age groups: 3 to 6 months (Experiment 1), 7 to 8 months (Experiment 2), and 10 to 12 months (Experiments 3 and 4). The neuroimaging data revealed age-related changes in patterns of activation to shape and speed information, mostly involving posterior parietal areas, some of which were predicted and others that were not. We suggest that these changes reflect age-related differences in the perceptual and/or cognitive processes engaged during the task.